(untitled) (Knjiženstvo, časopis za studije književnosti, roda i kulture, 2023)
Rewriting Academia : The Development of the Anglicist Women’s and Gender Studies of Continental Europe / Renate Haas (ed.). – 1. Edition. Includes index. Frankfurt am Main: Peter Lang, 2015, 442 pp., ISBN 978-3-631-66985-3 (hb), E-ISBN 978-3-653-06121-5 (e-book)